Effect of Fermented Cow and Soymilk as Probiotic on Energy Metabolism and Nutrient Retention in Broiler Chicken - Rusmana, Denny; Adriani , Lovita (International Journal of Poultry Science, 2020)
Background and Objective: Probiotics have been reported to have a positive effect on gut morphology and absorption of nutrients in poultry birds. Therefore, the present study was carried out to evaluate the effect of fermented cow and soymilk on energy metabolism and nutrient retention of broiler chicken. Materials and Methods: A total of 100-day old chick were allocated to 4 treatment groups in a complete randomized design (CRD) and each treatment was replicated 4 times with 5 chicken in each replicate. The treatments consisted of basal feed T0 (control), T1 (basal feed+100% fermented cow milk), T2 (basal feed +75% fermented cow milk +25% fermented soy milk) and T3 (basal feed+50% fermented cow milk +50% fermented soy milk. Results: The results show that Apparent metabolizable energy (AME), Apparent metabolizable energy with nitrogen (AMEn), retention of dry matter (DM) and nitrogen are significantly (p